Cognition-Oriented Treatments for Older Adults: a Systematic Overview of Systematic Reviews - Gavelin, Hanna Malmberg (Neuropsychol Rev, 2020)
Cognition-oriented treatments – commonly categorized as cognitive training, cognitive rehabilitation and cognitive stimulation – are promising approaches for the prevention of cognitive and functional decline in older adults. We conducted a systematic overview of meta-analyses investigating the efficacy of cognition-oriented treatments on cognitive and non-cognitive outcomes in older adults with or without cognitive impairment. Review quality was assessed by A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR). We identified 51 eligible reviews, 46 of which were included in the quantitative synthesis. The confidence ratings were “moderate” for 9 (20%), “low” for 13 (28%) and “critically low” for 24 (52%) of the 46 reviews. While most reviews provided pooled effect estimates for objective cognition, non-cognitive outcomes of potential relevance were more sparsely reported. The mean effect estimate on cognition was small for cognitive training in healthy older adults (mean Hedges’ g = 0.32, range 0.13–0.64, 19 reviews), mild cognitive impairment (mean Hedges’ g = 0.40, range 0.32–0.60, five reviews), and dementia (mean Hedges’ g = 0.38, range 0.09–1.16, seven reviews), and small for cognitive stimulation in dementia (mean Hedges’ g = 0.36, range 0.26–0.44, five reviews). Meta-regression revealed that higher AMSTAR score was associated with larger effect estimates for cognitive outcomes. The available evidence supports the efficacy of cognition-oriented treatments improving cognitive performance in older adults. The extent to which such effects are of clinical value remains unclear, due to the scarcity of high-quality evidence and heterogeneity in reported findings. An important avenue for future trials is to include relevant non-cognitive outcomes in a more consistent way and, for meta-analyses in the field, there is a need for better adherence to methodological standards. PROSPERO registration number: CRD42018084490. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11065-020-09434-8) contains supplementary material, which is available to authorized users.